THE INFLUENCE OF PRODUCT QUALITY, BRAND IMAGE, AND ELECTRONIC WORD OF MOUTH ON PURCHASING DECISIONS (STUDY ON MIXUE PRODUCTS IN BOGOR CITY) - Rafli Arjuna Kusumanegara; Nobelson Nobelson (Program Studi Manajemen Fakultas Ekonomi Universitas Palembang, 2023)
Currently frozen beverage sales in Indonesia are indicated to change over time,fluctuating from year to year, besides that Indonesia is number one as a country thatconsumes the most frozen drinks and ice cream in Southeast Asia, This study is aquantitative study, conduct aims to find out whether the variable Purchasing decision isinfluenced by Product Quality variables, Brand Image, and Electronic Word of Mouth. Byusing non-probability sampling techniques and purposive sampling methods. Data collectionis carried out by distributing questionnaires online and offline to prospective respondents.The analysis tool used is SmartPLS 3.0.0. Furthermore, the results obtained from this studyshow that product quality variables and brand image have a significant influence onpurchasing decisions. Electronic Word of Mouth has no significant effect on purchasingdecisions.